Conferring doorman characteristic and superior nano-scratch stability to graphene oxide membranes via tailoring channel microenvironment. (2nd September 2022) - Meng, Wenting; Li, Nan; Min, Chunying; Shi, Jie; Zhu, Bo; Liu, Liangsen; Liu, Shengkai; Shao, Ruiqi; Xu, Zhiwei; Cai, Zhijiang
Abstract : Graphene oxide (GO) membranes with doorman characteristic, tunable nanochannel microenvironment and high interfacial adhesion were fabricated. Abstract : Graphene oxide (GO) membranes with doorman characteristic, tunable nanochannel microenvironment and high interfacial adhesion were fabricated. Herein, polyethyleneimine (PEI) molecules were selected for bridging, reducing and intercalating the GO nanosheets in GO-PEI membranes. Moreover, the optimal amount of PEI molecules facilitated the expansion and alignment of the transfer channels with the spacing of 0.93 nm to 1.52 nm. In particular, the GO nanosheets undertook deoxidations twice under the action of a strong alkaline NaOH solution and PEI molecules, which led to more structural defects and certain wrinkles for providing extra water transfer channels. On this basis, PEI molecules exhibited doorman characteristics at different pH values. As the state-of-the-art technology, the nano-scratch tests showed that the interfacial adhesion of the GO-PEI membrane (18.62 μN) bridged by PEI was nearly 9 times stronger than that of the pure GO membrane (2.15 μN).